Molecular characteristics of antibiotic-resistant Escherichia coli and Klebsiella pneumoniae strains isolated from hospitalized patients in Tehran, Iran - Javad Yasbolaghi Sharahi; Ali Hashemi; Abdollah Ardebili; Sara Davoudabadi (BMC, 2021)
Abstract Background We evaluated the distribution of carbapenem and colistin resistance mechanisms of clinical E. coli and K. pneumoniae isolates from Iran. Methods 165 non-duplicate non-consecutive isolates of K. pneumoniae and E. coli were collected from hospitalized patients admitted to Iran's tertiary care hospitals from September 2016 to August 2018. The isolates were cultured from different clinical specimens, including wound, urine, blood, and tracheal aspirates. Antibiotic susceptibility testing was performed by disc diffusion and microdilution method according to the Clinical and Laboratory Standards Institute (CLSI) guideline. The presence of extended spectrum β-lactamases (ESBLs) genes, carbapenemase genes, as well as fosfomycin resistance genes, and colistin resistance genes was also examined by PCR-sequencing. The ability of biofilm formation was assessed with crystal violet staining method. The expression of colistin resistance genes were measured by quantitative reverse transcription-PCR (RT-qPCR) analysis to evaluate the association between gene upregulation and colistin resistance. Genotyping was performed using the multi-locus sequencing typing (MLST). Results Colistin and tigecycline were the most effective antimicrobial agents with 90.3% and 82.4% susceptibility. Notably, 16 (9.7%) isolates showed resistance to colistin. Overall, 33 (20%), 31 (18.8%), and 95 (57.6%) isolates were categorized as strong, moderate, and weak biofilm-producer, respectively. Additionally, bla TEM, bla SHV, bla CTX-M, bla NDM-1, bla OXA-48-like and bla NDM-6 resistance genes were detected in 98 (59.4%), 54 (32.7%), 77 (46.7%), 3 (1.8%), 17 (10.30%) and 3 (1.8%) isolates, respectively. Inactivation of mgrB gene due to nonsense mutations and insertion of IS elements was observed in 6 colistin resistant isolates. Colistin resistance was found to be linked to upregulation of pmrA-C, pmrK, phoP, and phoQ genes. Three of bla NDM-1 and 3 of bla NDM-6 variants were found to be carried by IncL/M and IncF plasmid, respectively. MLST revealed that bla NDM positive isolates were clonally related and belonged to three distinct clonal complexes, including ST147, ST15 and ST3299. Conclusions The large-scale surveillance and effective infection control measures are also urgently needed to prevent the outbreak of diverse carbapenem- and colistin-resistant isolates in the future.